2011
DOI: 10.3390/molecules16053933
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Glycosides of Glucuronic, Galacturonic and Mannuronic Acids: An Overview

Abstract: Uronic acids are carbohydrates present in relevant biologically active compounds. Most of the latter are glycosides or oligosaccharides linked by their anomeric carbon, so their synthesis requires glycoside-bond formation. The activation of this anomeric center remains difficult due to the presence of the electron-withdrawing C-5 carboxylic group. Herein we present an overview of glucuronidation, mannuronidation and galacturonidation reactions, including syntheses of prodrugs, oligosaccharides and stereochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 75 publications
(74 reference statements)
0
28
0
Order By: Relevance
“…A direct approach using 2-azido-2-deoxymannuronyl donor 2 and acceptor 4 gave a low yield of disaccharide probably due to low reactivity of uronyl donors (Scheme S2). [17] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A direct approach using 2-azido-2-deoxymannuronyl donor 2 and acceptor 4 gave a low yield of disaccharide probably due to low reactivity of uronyl donors (Scheme S2). [17] …”
mentioning
confidence: 99%
“…Probably, the carboxylic acid of the acceptor reduced the reactivity of the neighboring C-4 alcohol thereby complicating the glycosylation. [17a] …”
mentioning
confidence: 99%
“…12,33,34 This may be due to the deactivating effect of the electron-withdrawing C-5 carboxylic group, making the galacturonidation particularly challenging. 35 In addition, in their efforts to assess the influence of a pyranosyl C-5 carboxylate ester on the stereochemical outcome of glycosylation reactions, van der Marel and coworkers demonstrated that a C-5 ester is 1,5- cis or β-directing as opposed to C-5 methylene oxybenzyl, which induces little selectivity. 36 This is reflected in the synthesis of the Sphingomonas glycolipid 6 by Seeberger et al , who found that even after extensive optimization (including galactose protecting groups), glycosylation was achieved with a maximum 4.2:1 ratio of the α- and β-anomers.…”
Section: Resultsmentioning
confidence: 99%
“…This task is challenging in carbohydrate chemistry due to the low reactivity of the corresponding glycuronic donors. 12 In the case of baicalin, it is even more challenging because the glucuronic residue is attached to a phenolic hydroxyl group rather than an alkyl hydroxyl group. Phenolic -OHs are known as lowyielding glycosylation acceptors due to their reduced nucleophility than that of their alcohol counterparts.…”
Section: Introductionmentioning
confidence: 99%